“VERBAL LINKING” AS A LANGUAGE CATEGORY IN ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2023)
In the article “verbal linking” in English and Uzbek languages, such as the connections between noun construction elements represented with the help of a verb unit have been researched.